Nanosized spherical and porous films based on poly(acrylic acid)-b-poly(N-phenylmaleimide) and poly(hydroxypropyl metacrylate)-b-poly(N-phenylmaleimide): Optical, thermal and morphological properties. Issue 1 (1st January 2020) - Pizarro, Guadalupe del C.; Marambio, Oscar G.; Jeria-Orell, Manuel; Oyarzún, Diego P.; Martin-Trasanco, Rudy; Sánchez, Julio
Abstract: In the present work, we have investigated the effect of the chemical structure, concentration and solvent on the morphological properties of diblock copolymers at a certain percentage of humidity. The block copolymers were prepared using the atom transfer radical polymerization (ATRP) to obtain well-defined amphiphilic block copolymers with controlled molecular weights and molecular weight narrow size distribution. Breath figures (BF) method was used for the formation of porous materials or microspheres under certain experimental conditions, where the role of the water involved is crucial. The self-assembly behavior of these copolymers in presence of water drops was investigated by optical microscopy and scanning electron microscopy (SEM) exhibiting their ability to form spherical micelles under certain experimental conditions. The morphological properties of the films indicated that these diblock copolymers promotes the coexistence of porous and microspheres in the surface of the films.